Implementation of Transport Infrastructure PPPs in the Czech Republic, Finland, Poland and Slovakia – A Comparative Analysis on National Contexts - Leviakangas, Pekka; Witz, P.; Lukasiewicz, A.; Szekeres, K. (Inderscience Publishers, 2015)
Although the concept of public-private partnership has been adopted in most countries in the world, relatively little attention has been paid to the ways PPP has been implemented and how the national political, legislative and administrative context affect the success of public-private partnerships. This paper compares the PPP experience of the three post-communist countries - the Czech Republic, Slovakia and Poland - with that of Finland. It shows that although PPP was equally alien to the countries' political and administrative systems, Finland has managed to implement PPPs without any serious problems while in the three transitive countries the same process produced numerous major failures and controversies. Several factors behind this contrast are identified including political and institutional stability, different nature of regulatory frameworks and established managerial practices. In the end, important lessons are drawn from the cases for both the most developed and transitive countries implementing PPPs.